Penggunaan Media Gambar Seri Dalam Meningkatkan Keterampilan Menulis Narasi Murid Kelas III SDI Ra’ong Kabupaten Manggarai Barat - Saufanti Satria; Rosmini Madeamin; Andi Aco Karumpa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The main problem in this research is how to improve students' narrative writing skills using series of image media. The aim of this research is to improve the narrative writing skills of class III students at SDI Ra'ong, West Manggarai Regency using series image media. This research is classroom action research or what is called CAR (Classroom Action Research). The subjects in this research were class III students at SDI Ra'ong, West Manggarai Regency in the 2023/2024 academic year with a total of 10 students. There are 4 male students and 6 female students. The data collection techniques used in this research are tests, observation and documentation. The results of the research showed that there was an increase in student learning outcomes from students from cycle I to cycle II, where in cycle I the percentage of student completion was 30%, while in cycle II the percentage reached 100%. Based on the results of the research above, it can be concluded that the learning outcomes of class III students at SDI Ra'ong, West Manggarai Regency have increased after implementing the use of series image media.